Economic impacts of climate change and adaptation policy in Malaysia / Nazneen Jabin - Jabin, Nazneen (2015)
Malaysia is experiencing some unusual combination of droughts and extreme rainfall in recent years. As a consequence, crop production is likely to fall significantly in the years to come. There is hardly any strategy i.e. adaptation policy in effect to cope with this issue. The impacts and costs of adaptation measures cannot be optimally determined on a global basis as they can vary from region to region, between countries or even within a country. Moreover, due to the lack of adequate quantitative adaptive models, the economic impacts, effectiveness, and cost assessment for adaptation policies cannot be ascertained. The study of cost effectiveness for adaptation action is necessary for the government to formulate an appropriate adaptation policy. Given the absence of existing measures, this study develops a quantitative adaptive model termed the Malaysian Climate and Economy (MCE) model based on the dynamic Computable General Equilibrium (CGE) model structure to examine the climate change impacts of the adaptation policy and identify the macroeconomic influences on the overall economy. As agriculture is the most vulnerable sector to climate change, we focus our study on this particular sector and analyse its impacts on specific crops (sub sectors) within the agriculture sector. This study seeks to determine the long-term and optimal adaptation measures by comparing the adaptation cost versus the economic losses due to climate change in Malaysia. Our findings indicate that the optimum level of adaptation varies over time with continued economic growth and the costs of adaptation tend to increase as well. Findings show that over the hundred year projection period, the optimum level of adaptation tends to be within the range of 13 to 34 percent of gross damages. The associated costs of adaptation varies from 32 million to 1,735 million ringgits. This indicates that the optimal adaptation policy is effective for Malaysia in terms of reducing the negative impacts of climate change (i.e. in terms of monetary damages). The findings indicate that benefits of adaptation policy are almost seven times the cost of adaptation for each time segment. Using this optimal adaptation information, we suggest policy choices for the national policy framework (i.e. Malaysian National Policy on Climate Change, 2009) so that the government can achieve an optimal adaptation decision to better manage the adverse consequences of climate change. Such actions and measures are adjudicated to assure cohesive participation of all concerned development bodies including government and non-government organisations along with local communities towards achieving the appropriate climate change response.